Functions of Drosophila Toll/NF-κB signaling in imaginal tissue homeostasis and cancer - Brutscher, Fabienne; Basler, Konrad (Frontiers in Cell and Developmental Biology, 2025)
The Toll/NF-κB pathway plays a central role in patterning the Drosophila embryo and in orchestrating the innate immune response against microbial infections. Both discoveries were associated with a Nobel Prize award and led to the recognition of the Toll-like receptor pathway in mammals, which has significant implications for diseases. Recent discoveries have revealed that the Toll/NF-κB pathway also maintains epithelial homeostasis of imaginal tissues during development: local Toll/NF-κB signaling activity monitors internal cellular fitness, and precancerous mutant cells can trigger systemic Toll/NF-κB pathway activation. However, this signaling can be exploited in diseases like cancer, in which Toll/NF-κB signaling is often co-opted or subverted. Various models have been proposed to explain how Toll/NF-κB signaling contributes to different types of cancer. Here we provide an overview of the functions of Toll/NF-κB signaling in imaginal tissue homeostasis with a focus on their misuse in pathological contexts, particularly their significance for tumor formation.